Burkholderia pseudomallei detection in surface water in southern Laos using Moore's swabs. - Vongphayloth, K; Rattanavong, S; Moore, C; Phetsouvanh, R; Wuthiekanun, V; Sengdouangphachanh, A; Phouminh, P; Newton, P; Buisson, Y (2012)
The causal agent of melioidosis, Burkholderia pseudomallei, has been cultured from paddy fields in the Lao PDR. We carried out a pilot study to examine the relationship between bacterial soil contamination and that of nearby surface waters in Saravane Province. Soil sampling was conducted at a depth of 30 cm (100 holes in a 45 × 45 m grid) at two sites, East and West Saravane. Moore's swabs were used for water sampling of paddy fields, lakes, rivers, boreholes, and storage tanks within 2 km of the two soil sampling sites. B. pseudomallei from soil and water were cultured on Ashdown's agar. Thirty-six percent and 6% of water samples collected around East and West Saravane, respectively, were culture positive for B. pseudomallei. Low pH and high turbidity were independently associated with culture of B. pseudomallei. Most positive water samples were from the Sedone River, downstream of the East Saravane site. Moore's swabs are simple and inexpensive tools for detecting B. pseudomallei in surface waters.